4
$\begingroup$

Let $X_1,\cdots,X_n$ and $Y_1,\cdots,Y_n$ are iid from $X\sim \operatorname{Exponential}(\lambda)$ and $𝑌\sim\operatorname{Bernoulli}(p)$ respectively, where $X$ and $Y$ are independent.

Given $n,\lambda,p$ and $c$, we consider computing $$ P\left(\sum_{i=1}^nX_iY_i > c \right) $$ Let $S=\sum_{i=1}^nS_i=\sum_{i=1}^nX_iY_i$. I try to derive its density and then I compute the underlying probability by integral, similar as Edmond Levy with the hypo-exponential density. However, I can not get the density of $S_i$; see also here and here for discussions. Any suggestions?

$\endgroup$
8
  • 2
    $\begingroup$ $$ \begin{align} & \Pr\left(\sum_{i=1}^nX_iY_i > c \right) = \operatorname E\left( \Pr\left( \sum_{i=1}^n X_i Y_i>c \,\, \Bigg\vert\,\, \sum_{i=1}^n Y_i \right) \right) \\ {} \\ = {} & \sum_{j=0}^n \Pr \left( \sum_{i=1}^n X_i Y_i >c \,\, \Bigg\vert\,\, \sum_{i=1}^n Y_i = j \right) \Pr\left( \sum_{i=1}^n Y_i = j \right) \\ {} \\ = {} & \sum_{j=0}^n \Pr\left( \operatorname{Gamma}(j,\lambda)>c \right) \binom n j p^j (1-p)^{n-j} \\ {} \\ = {} & \sum_{j=0}^n \int_c^\infty \frac 1{\Gamma(j)} ( \lambda u)^{j-1} e^{-\lambda u} (\lambda\,du) \binom n j p^j(1-p)^{n-j} \end{align} $$ $\cdots$ $\endgroup$ Commented Oct 4, 2023 at 3:53
  • 2
    $\begingroup$ I might start like that and go on from there. Maybe I'll post something later. $\endgroup$ Commented Oct 4, 2023 at 3:54
  • 2
    $\begingroup$ When $\sum Y_i = 0$, I think that $S$ must be defined as zero (empty sum) so the distribution of $S$ has an atom at $S=0$. If so, for $c$ positive and finite $\text{Pr}(S > c) =0$. $\endgroup$
    – Yves
    Commented Oct 4, 2023 at 5:17
  • 1
    $\begingroup$ The "internal" integral ($\int_c^{\infty } \lambda \exp (-\lambda u) (\lambda u)^{j-1} \, du$) evaluates to $\Gamma (j,c \lambda )$. Plugging that in and finding that the term with $j=0$ is zero, the general result is $\sum _{j=1}^n \frac{p^j \binom{n}{j} (1-p)^{n-j} \Gamma (j,c \lambda )}{\Gamma (j)}$. For $n=1,2,3$ this simplifies to $p e^{-c \lambda }$, $p e^{-c \lambda } (p (c \lambda -1)+2)$, and $\frac{1}{2} p e^{-c \lambda } (p (6 c \lambda +p (c \lambda (c \lambda -4)+2)-6)+6)$, respectively. And, yes, @MichaelHardy did all of the heavy lifting. $\endgroup$
    – JimB
    Commented Oct 4, 2023 at 15:01
  • 2
    $\begingroup$ This is a mixture of Gamma distributions $Ga(k,\lambda)$ with the mixture weights being Binomial $\mathcal B(n,p)$. $\endgroup$
    – Xi'an
    Commented Oct 4, 2023 at 16:23

2 Answers 2

3
$\begingroup$

Here is a less-than-complete answer: \begin{align} & \Pr\left(\sum_{i=1}^nX_iY_i > c \right) = \operatorname E\left( \Pr\left( \sum_{i=1}^n X_i Y_i>c \,\, \Bigg\vert\,\, \sum_{i=1}^n Y_i \right) \right) \\ {} \\ = {} & \sum_{j=0}^n \Pr \left( \sum_{i=1}^n X_i Y_i >c \,\, \Bigg\vert\,\, \sum_{i=1}^n Y_i = j \right) \Pr\left( \sum_{i=1}^n Y_i = j \right) \\ {} \\ = {} & \sum_{j=0}^n \Pr\left( \operatorname{Gamma}(j,\lambda)>c \right) \binom n j p^j (1-p)^{n-j} \\ {} \\ = {} & \sum_{j=0}^n \int_c^\infty \frac 1{\Gamma(j)} ( \lambda u)^{j-1} e^{-\lambda u} (\lambda\,du) \binom n j p^j(1-p)^{n-j} \\ {} \\ = {} & \sum_{j=0}^n \frac 1 {\Gamma(j)} \binom n j p(1-p)^{n-1} \int_c^\infty \left( \frac{\lambda up}{1-p} \right)^{j-1} e^{-\lambda u} (\lambda\, du) \end{align}

$\endgroup$
1
  • $\begingroup$ It is enough for me! Tks for the clue! @MichaelHardy $\endgroup$
    – John Stone
    Commented Oct 8, 2023 at 14:34
1
$\begingroup$

To add to @MichaelHardy 's answer the "internal" integral is an incomplete gamma:

$$\int_c^{\infty } \lambda \exp (-\lambda u) (\lambda u)^{j-1} \, du=\Gamma(j,c \lambda)$$

So the desired probability is

$$ \Pr\left(\sum_{i=1}^nX_iY_i > c \right) =\sum_{j=1}^n {\binom{n}{j}}p^j (1-p)^{n-j} \Gamma(j,c \lambda)/\Gamma(j)$$

Note that the sum on the righthand side starts at $j=1$ rather than $j=0$ as

$$\Pr\left(\sum_{i=1}^n X_i Y_i > c \,\, \Bigg\vert\,\, \sum_{i=1}^n Y_i=0\right)=0$$

If one doesn't have access to an incomplete gamma function, then the following is an equivalent result

$$\ \Pr\left(\sum_{i=1}^nX_iY_i > c \right) =e^{-c \lambda} \sum _{j=1}^n \binom{n}{j} p^j (1-p)^{n-j} \sum _{i=0}^{j-1} \frac{(c \lambda )^i}{i!}$$

As a partial check suppose $n=7$, $p=1/3$, $\lambda=2$, and $c=1$. The formula gives $\frac{348049}{98415 e^2}\approx 0.478619$. Some R code to perform simulations:

p <- 1/3
c <- 1
lambda <- 2
n <- 7
nsim <- 1000000

set.seed(12345)
z <- rowSums(matrix(rexp(n*nsim, lambda)*rbinom(n*nsim, 1, p), nrow=nsim))
prob <- length(z[z>c])/nsim
# [1] 0.478865

For small values of $n$ one can construct the following table:

Table of probabilities for small values of n

$\endgroup$
1
  • $\begingroup$ Yes, you're right! I like your R simulation parts! Actually, we can use sapply and pgamma in R to compute its exact solution according to the clues of you and Michael Hardy as 0.4786192. Tks!@JimB $\endgroup$
    – John Stone
    Commented Oct 8, 2023 at 14:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.